Deep-diving into the relationship between corporate social performance and corporate financial performance: A comprehensive investigation of previous research - David Robles-Elorza; Leire San-Jose; Sara Urionabarrenetxea (European Research on Management and Business Economics (ERMBE), 2023)
Corporate social performance (CSP) and corporate financial performance (CFP) have been studied widely in the last fifteen years. These major efforts in research and publication might have been expected to produce aligned results but is it not the case; this paper aims to study why there is no consensus among them. By using the bibliometric data obtained from Scopus, this paper looks at four bibliometric indicators (journals, authors, countries, areas) for published work. We look for papers between 1977 and 2018 and identify a total of 371. The findings reveal that there are at least five key journals publishing in CSP-CFP relationship. There is a lack of co-occurrence between authors, regarding areas, two distinct perspectives are detected: one based on sustainability and social responsibility and the other linked more closely to marketing, and both perspectives can be connected via stakeholder theory. It contributes using bibliometric approach, it shows a reason to align the results around the relationship between CSP-CFP and open the windows to create a theory. Finally, the findings of this paper provide insights to the researchers on the development of social responsibility. The disparity of results in this line enriches analysis but does not outcome in a single line of contribution to science, thus decreasing the potential for channelling studies into a single theory. This only seems possible if contributions can be focused on the nexus that unites them: stakeholder theory.
Keywords: M14; 650; Corporate financial performance; Corporate social performance; Sustainability; Stakeholder theory